Desarrollo de un sistema SCADA para una estación de bombeo de agua a presión constante. - Almachi Chiguano, Jonathan Wladimir (2021)
The objective of this project is the development and implementation of a SCADA (Supervisory Control and Data Acquisition) system applied to a constant pressure water pumping station related to the lack of practices in the area of automation and control of industrial processes through programmable logic controllers (PLC) for the analysis of data acquisition either locally or remotely as available to the user. The project consists of three stages, the first stage focuses on the collection of information on water pumping systems and methods for their control. The second stage focuses on the construction of the plant for which the structure is designed in the Inventor software and its structural analysis is performed with relation between the maximum allowable voltage and the equivalent voltage resulting in a safety coefficient (2.54), then the electrical, electronic and hydraulic elements needed for the start-up of the plant are established. Finally, the third stage establishes the operation of the module by programming a proportional, integral and derivative (PID) pressure controller in the PLC, and integrates the SCADA system in the Ignition software that performs the control and monitoring of the plant through TCP/IP communication. The results indicate that the best tuning method for the process is the Robust Lambda with a set point time of 237.6 seconds in transient regime with an over impulse of 0.21 % which establishes an acceptable tuning method as it does not have major oscillations in the stationary regime that tends to infinity. According to the set point value implemented, the time will change, taking into account that the higher the pressure, the shorter the settling time.